Estudo do processo de piroexpansão de feldspatos pegmatíticos e caracterização tecnológica do feldspato potássico - Fernando Antonio Nogueira de Oliveira (2001)
This dissertation presents the mineralogical and technological characterization of the perthitic potassic feldspar (microcline) from pegmatites of the Linópolis region, Minas Gerais, and the analysis of its behavior for the use in ceramic industry, highlighting its expansion duringheating. The studies of thermal expansion (boiling) have been accomplished according to the following: 1) physical analyses: macroscopic mineralogical analysis, sampling preparation, specificgravity, microscopic optics, and Xray difratometry; 2) chemical analyses: loss of ignition, Xray fluorescence spectroscopy, and infrared absorption spectroscopy. The technological tests have included the heating of brickshaped samples at three temperatures (T1 = 1.150°C; T2 = 1.200°Cand T3 = 1.250°C), also ore powdered cones have been heated under 1.250°C. The results have shown that the feldspar samples, when submitted to heating present decreasing of specific gravity, volume increase and loss of mass. The microscopic analysis shows the increasing vitrification of the ore component phases (microcline and albite), corroborated by Xray diffraction analysis. During the X-ray fluorescence analysis gradual loss of Na2O and increase of Al2O3 rates could be clearly noticed. The infrared absorption spectrometry analysis of the natural samples showns transmittance bands related to the tetrahedra SiO4 in the region between 1.1351.035cm1, and transmittance bands related to Al O bonds in the region 780720cm1. Samples submitted to heating at T1, T2 e T3 suffer distortion on the SiO and AlO transmittance bands. The whole degeneration of the microcline structure, followed by the vitrification of the material, occurs around 1.250°C and is marked by the disappearance of the bands relative to the SiO and AlO bonds. The thermal expansion could be explained by variations in the amount of albitic phase, the density of distribution of the albitic phase within the potassic matrix as well as the increasing fluid expelling during heating.